2020
DOI: 10.1152/ajpregu.00224.2019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of exercise training and estrogen supplementation on mast cell-mediated doxorubicin-induced cardiotoxicity

Abstract: Cardiac inflammation has been proposed as one of the primary mechanisms of anthracycline-induced acute cardiotoxicity. A reduction in cardiac inflammation might also reduce cardiotoxicity. This study aimed to evaluate the potential of estrogen therapy and regular exercise on attenuating cardiac inflammation in the context of doxorubicin-induced cardiomyopathy. Ovariectomized rats were randomly allocated into estrogen supplementation, exercise training, and mast cell stabilizer treatment groups. Eight weeks aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…However, the chronic phase in the present study showed a significant increase of cardiac biomarkers in comparison with the group-specific control, suggesting that mitochondrial redox status is not the dominant factor contributing to the observed mitochondrial damage. Interestingly, we noticed the presence of degranulated mast cells in the heart of chronic group, which aggravate the possible role of the bioactivated components of DOX [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the chronic phase in the present study showed a significant increase of cardiac biomarkers in comparison with the group-specific control, suggesting that mitochondrial redox status is not the dominant factor contributing to the observed mitochondrial damage. Interestingly, we noticed the presence of degranulated mast cells in the heart of chronic group, which aggravate the possible role of the bioactivated components of DOX [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reductions in these pro-apoptotic markers indicate exercise can decrease cardiomyocyte apoptosis in the setting of DOX leading to preserved heart structure and function. Important to note, these studies showed similar results in reducing pro-apoptotic markers despite the length of the training program, which varied from as short as 2 weeks to as long as 14 weeks [34,36,38].…”
Section: Basic Science: Aerobic and Resistance Exercisesmentioning
confidence: 66%
“…They found that exercise training was able to attenuate DOX-induced increases in pro-apoptotic proteins including Bax and cleaved caspase 3 [36]. The ability of AE to attenuate cleaved caspase 3 activity has also been observed in other chronic exercise studies [34,38]. The reductions in these pro-apoptotic markers indicate exercise can decrease cardiomyocyte apoptosis in the setting of DOX leading to preserved heart structure and function.…”
Section: Basic Science: Aerobic and Resistance Exercisesmentioning
confidence: 72%
See 1 more Smart Citation
“…These actions may explain why ovariectomized (OVX) rodents exhibit exacerbated DOX cardiotoxicity compared to DOX-treated cycling females [44]. Further supporting the protective role of estrogen in DOX cardiotoxicity are data showing the attenuation of DOX cardiac effects in OVX rodents following supplementation with estrogen [48,123]. The role of testosterone in DOX-induced cardiotoxicity, however, remains unclear, with studies suggesting exacerbated cardiotoxicity [94], no change in cardiac function [48], or attenuation of DOXinduced senescence [124] and oxidative stress [125].…”
Section: Contribution Of Sex Hormones To the Development Of Doxorubicmentioning
confidence: 99%